Clinical Outcomes Comparison in Administration of Secretome vs Hyaluronic Acid in Patients with Knee Osteoarthritis Kellgren-Lawrence Grade I-III - Aryana, I Gusti Ngurah Wien; Suyasa, I Ketut; Dharmayuda, Cokorda Gde Oka; Febyan; Gunawan, Dary (Indonesian Journal of Medicine, 2024)
Background: The prevalence of OA in Indonesia is predicted to reach more than 20% of the population aged over 60 years in 2050, with a high risk of disability. So far, early treatment of osteoarthritis in the form of administering hyaluronic acid has not been completely satisfactory and tends to be progressive until ending in more invasive operative therapy. This study aimed to compare the clinical outcomes between secretome injection and hyaluronic acid in patients with Kellgren-Lawrence grade I-III knee osteoarthritis. Subjects and Method: This was a single-blind experimental study. This study was conducted in the orthopedic polyclinic at General Hospital Prof. Dr. I.G.N.G. Ngoerah Bali. A total sample of 36 knee osteoarthritis patients was selected using permuted block sampling with randomization. The sample was divided into two groups, (1) secretome (intervention group) and (2) hyaluronic acid (control group). The independent variables were secretome injection and hyaluronic acid injection. The dependent variable was pain. Pain was measured using Western Ontario and McMaster University (WOMAC), Knee Osteoarthritis Outcome Score (KOOS), Visual Analog Score (VAS), and Patient-Reported Outcome Measure (PROM). Results: Based on gender, there are more women than men and the right foot is more affected at 58.3%. Functional score parameters in each secretome and hyluronic acid group were compared between the 3rd and 6th months of follow-up. Pain in the hyaluronic acid group was lower than in the secretome group. Conclusion: Hyaluronic acid has better effect in pain reduction than secretome. Further studies could explore the underlying mechanisms and potential long-term effects to better understand these differences in pain outcomes.